Model-Eliciting Activities (MEAs) Approach to Mathematical Problem Solving Ability at MA DDI Alliritengae - Erna wati; Pertiwi Indah Lestari; Dedy Setyawan; Siti Aminah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
This experimental research aims to assess the impact of the Model-Eliciting Activity (MEAs) learning approach on the mathematical problem-solving abilities of class XI students at MA DDI Alliritengae. Utilizing a quasi-experimental method with a Non-Equivalent Control Group Design, the study involved pre-test and post-test evaluations of both control and experimental groups. Simple Random Sampling was employed for sample selection. The research revealed that, initially, students in both groups exhibited low mathematical problem-solving abilities. Post-test results indicated that while the control group showed only minor improvements, remaining mostly at low or medium criteria, the experimental group demonstrated significant improvements, with most indicators reaching a high category. Hypothesis testing yielded a sig. (2-tailed) value of 0.000, indicating a significant effect of the MEAs approach on students' mathematical problem-solving skills. Thus, the study concludes that the MEAs approach effectively enhances mathematical problem-solving abilities, outperforming traditional lecture methods